Theorizing cultural HRD: an emancipatory structures approach - Anderson, Valerie; Poell, Rob; Mohd Rasdi, Roziah (Routledge, 2024)
The HRD field, in its current situation as it approaches the second quarter of the twenty-first century, is at a crossroads. Although theories of HRD that have been developed in Western Europe and North America have served the field well, they represent the voices and experiences of less than 25% of the world’s population. This paper questions the enduring dominance of Western-cultural HRD, and argues for transformation of the discipline to be inclusive and equitable but also reflective of the global mosaic of human knowledge, wisdom, and practice. We critically consider literature arguing for a generalised theorisation of HRD and, grounded in our own different positional perspectives, we propose and discuss a new term Cultural HRD, which is distinct from National HRD (NHRD) and Indigenous HRD, as a way forward for HRD theorising. We illustrate our proposed concept through describing what we term Islamic-cultural HRD and contrasting this with Western-cultural HRD. Prompted by our concerns relating to the under-representation of cultural HRD theorisation, we further argue for a new emancipatory structures approach to theorising, to pivot HRD towards a more equitable and context-sensitive discipline that can both explain and foster human and organisational development across diverse global contexts.